Trade-offs between fisheries, offshore wind farms and marine protected areas in the southern North Sea – Winners, losers and effective spatial management. (June 2023) - Püts, Miriam; Kempf, Alexander; Möllmann, Christian; Taylor, Marc
Abstract: There is an increasing need for marine spatial planning in the North Sea given the multiple uses with competing objectives. Plans to increase renewable energy production by establishing offshore wind farms (OWFs) are likely to coincide with existing and planned marine protected areas (MPAs), with obvious incompatibilities relating to conservation goals. Both will restrict fishing activities to varying degrees, thus a framework is needed to assess possible trade-offs to differing stakeholders and ecosystem health. Using a spatially-explicit trophic model, ecosystem response to different types of spatial closures to fisheries was evaluated using a variety of indicators relating to ecosystem health and fisheries productivity in the southern part of the North Sea. Additionally, hypothetical MPAs designated with specific ecological objectives in mind were tested. Scenario outcomes suggest that closures may need to be accompanied with additional fisheries management measures to avoid unintended negative impacts outside the closed areas. Furthermore, size and placement of spatial closures are important factors influencing overall benefits and losses in terms of ecological health and fisheries yield. One particular hypothetical large-scale closure, designed with the goal of protecting areas with high biodiversity, performed better in terms of indicators and trade-offs than the more fragmented, currently planned and existing closures. Although model outcomes have to be treated with care, the spatially-explicit food web modeling approach will likely aid in providing a more holistic evaluation of trade-offs between conservation objectives and fishing activities, which should contribute to a more target-oriented framework for the evaluation of closed areas. Highlights: Positive impact of fishing exclusion on ecological indicators inside closed area. Fishing effort reduction needed to counterbalance effects of effort redistributions. Placement and size of closure most important. Trade-offs not only between sectors, but also within food web. Closure of area with low fishing effort and high protective value performed best.